THE ROLE OF NATIONAL ARCHETYPES IN FORMULATING OF A VISION OF THE FUTURE OF RUSSIA - Ivanova, M.G. (RUDN Journal of Political Science, 2017)
The article discusses the conceptualization and formation of the image of the future of Russia in domestic and foreign policy. The author emphasizes the high heuristic potential of the civiliza-tional approach and the theory of archetypes of C.G. Jung. The author shows that the important role in shap-ing the image of future Russia should play psycho-political analysis of socio-cultural and operational code of Russia that should be carried out by the Russian political expert community.